2021
DOI: 10.3390/act10090221
|View full text |Cite
|
Sign up to set email alerts
|

Development and Performance Evaluation of a Precise Application System for Liquid Starter Fertilizer while Sowing Maize

Abstract: At present, liquid starter fertilizer (LSF) application technologies experience problems with low fertilizer utilization efficiency. In this study, we adopted a method of precise application of LSF near the seeds on seed bed in point form during sowing. A precise application system that can detect seed information in real time and control the solenoid valve to open automatically was developed for this method. The LSF supply system and detection control system were studied in detail. Field experiments were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The quality index of the length of LSF was 96.4%, the range of FA was 1.34 to 13.86 mL, and QID was 82.6%, which signifies the developed system meets the demands of precise LSF application [67]. Increasing MAP decreased the pH of the mineral fertilizer mixture (MF) from 8.0 (100% MAP) to <5.5; the target pH values of 5.8 and 7.0 were obtained, respectively, with 50% and 12.6% MAP in the MF; the pH values of the OMF (SPS + MF) varied from 5.8 (MF without SPS) to 6.0-6.9 (80% SPS + 20% MF), depending on the type of SPS.…”
Section: Precise Application Systemmentioning
confidence: 79%
See 2 more Smart Citations
“…The quality index of the length of LSF was 96.4%, the range of FA was 1.34 to 13.86 mL, and QID was 82.6%, which signifies the developed system meets the demands of precise LSF application [67]. Increasing MAP decreased the pH of the mineral fertilizer mixture (MF) from 8.0 (100% MAP) to <5.5; the target pH values of 5.8 and 7.0 were obtained, respectively, with 50% and 12.6% MAP in the MF; the pH values of the OMF (SPS + MF) varied from 5.8 (MF without SPS) to 6.0-6.9 (80% SPS + 20% MF), depending on the type of SPS.…”
Section: Precise Application Systemmentioning
confidence: 79%
“…For example, starter N fertilizer (classical and slow-release urea) deep placement reduced CH 4 emissions in comparison with surface broadcasting [64], which is a result of an increase in CH 4 oxidation stimulated by the high NH 4 + -N in localized bands and promoted by root growth in the deep soil [65,66]. The use of a self-propelled spoke wheel applicator to inject and deep place liquid fertilizer dissolved from crystalline of (NH 4 ) 2 HPO 4 (21-53-0) has increased maize establishment, production, and productivity [67]. In the cane study, maximum yields were observed when a cam-crank rocker combination mechanism deep placed the liquid fertilizer (ammonium nitrate mixed with water: 0.21 kg N L −1 ) at a rate of 100 kg N ha −1 [14,68,69].…”
Section: Subsurface Starter N-p-k Fertilization Placementmentioning
confidence: 99%
See 1 more Smart Citation
“…The tee pipe is widely utilized in numerous fields, including irrigation, water supply and drainage, agricultural fertilizer injection, and drainage systems. It is one of the essential parts of liquid transmission and distribution systems [1][2][3]. In transmission and distribution systems, the overall hydraulic losses are mostly attributed to the local resistance of the tees.…”
Section: Introductionmentioning
confidence: 99%